Odor-active constituents of Cedrus atlantica wood essential oil. (December 2017) - Uehara, Ayaka; Tommis, Basma; Belhassen, Emilie; Satrani, Badr; Ghanmi, Mohamed; Baldovini, Nicolas
Abstract: The main odorant constituents of Cedrus atlantica essential oil were characterized by GC-Olfactometry (GC-O), using the Aroma Extract Dilution Analysis (AEDA) methodology with 12 panelists. The two most potent odor-active constituents were vestitenone and 4-acetyl-1-methylcyclohexene. The identification of the odorants was realized by a detailed fractionation of the essential oil by liquid-liquid basic extraction, distillation and column chromatography, followed by the GC-MS and GC-O analyses of some fractions, and the synthesis of some non-commercial reference constituents. Graphical abstract: Highlights: This study reports the first characterization of Atlas cedarwood odorants by GC-O AEDA. The atlantones, previously reported as important odorants, were totally odorless in our assays with 12 panelists! Important (and up to now completely underestimated) odorants are 4-acetyl-1-methylcyclohexene and vestitenone.